Analisis Rantai Pasok (Supply Chain) Produk Daging Sapi di Rumah Potong Hewan Bangkong Sumbawa - Ramadhan, Gilang; Anggriani, Luluh (Fakultas Ilmu dan Teknologi Hayati Universitas Teknologi Sumbawa, 2025)
This research aims to analyze the supply chain of beef at the Bangkong and finance, as well as distribution efficiency in the beef marketing system. The method used is a survey method with a quantitative descriptive approach. Data collection was carried out through observation, interviews, and the distribution of questionnaires to farmers, traders, retailers, and consumers. The result show that the length of the supply chai affects the increasing sellng price of beef at the consumer level. The product flow goes from farmers to consumers through several intermediaters, while the flow of information and finance has not been efficiently integrated. The result of this stuy indicate that the farmer’share is 80% for farmer’s 80% for live cattle traders, 64% for retailers, and marketing efficiency is 2.8%. Costsin the Distribution costs, marketing margins, and farmer’s share indicate that the supply chain efficiency is still relatively low. Therefore, efforts to streamline distribution channels and improve coordination among stakeholders are necessary to enhance efficiency and stabilize beef prices in the market.